UJI KUALITAS PERKECAMBAHAN BENIH SORGUM (Sorghum bicolor L. Moench) BERBAGAI GENOTIPE LOKAL DARI SUMBA TIMUR - F. Zega, Andika Jonathan Brilliant; Kurnia, Theresa Dwi (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2025)
This study aims to evaluate the viability and vigor of sorghum seeds from four genotypes using the Rolled Paper Towel Method in Plastic, with rice straw paper as the germination medium. This method was chosen for its practicality, cost-effectiveness, and compliance with ISTA  standards. The results revealed variations in seed viability, growth rate, vigor index, and growth uniformity among genotypes. The Watar Hammu Rara Tadda and Watar Hammu Manipar Tadda genotypes demonstrated the best performance, with germination rates reaching 93%, growth rates exceeding 7.0, and high vigor indices. This research supports strategies for providing high-quality sorghum seeds to strengthen national food security, particularly in dryland areas.